The Honey Quality of Apis mellifera with Extrafloral Nectar in Lombok West Nusa Tenggara Indonesia - Erwan Erwan; Muhammad Harun; Muhammad Muhsinin (Journal of Science and Science Education, 2020)
The purpose of the present study was to analyze Apis mellifera honey's quality given extrafloral nectar feed from Arenga pinnata sap and Cocus nucifera sap as stimulatory nutrition. The chemical compositions of honey, such as reducing sugar content, sucrose content, the acidity of honey, moisture content, and diastase enzyme activity, were measured. The comparison between A. mellifera honey's chemical compositions on Arenga pinnata sap and Cocus nucifera sap ware was analyzed using the student t-test (GraphPad Instant Statistical Program). The result from the analysis of reducing sugar content showed that the A. mellifera honey from Cocus nucifera sap (73.69± 0.21%) had a higher (P<0.05) than the Arenga pinnata sap (60.15±2.13%). The significant diﬀerences (P<0.05) in the acidity of A. mellifera honey from Arenga pinnata sap (43.00±7.48) compared with Cocus nucifera sap (22.00±2.14). The sucrose content, moisture content, and diastase enzyme activity were not significant differences between the A. mellifera honey from Arenga pinnata sap compared with the A. mellifera honey from Cocus nucifera sap. In conclusion, the chemical compositions of A. mellifera honey with extrafloral nectar (Arenga pinnata sap and Cocus nucifera sap) are good quality and indicate that the honey falls under the limits of international standards. The A. mellifera honey from Cocus nucifera sap has a higher sugar reduction content and lower acidity than the A. mellifera honey from Arenga pinnata sap